Magic gaming studio / Meor Muhammad Hakimi Abd Malik...[et al.] - Abd Malik, Meor Muhammad Hakimi; Anuar, Muhammad Idham; Mohd Rodi, Mohammad Nazmil; Mohd Sapiny, Muhammad Muqri Aiman (2018)
This business plan is a new projected business that have been named as Magic Gaming Studio. The name of the company came from the agreement of all member of partnerships of the company itself. It shows that we provide a place to hang out and provide with the modern technologies to the customers. The name itself is easy to memorize and pronounce. As for the business, we are providing a bar and gaming stations to the customer. We prepare the room for prayer. As with these facilities that we are providing it can attract young adult and stress workers to have a chill at our place for them to release their tension. The bar will provide more to snack foods, so that the customer will get sugar rush for them to spend a day in our place. We are starting out our business with the total capital of RM 52,900 by the partners that contribute RM 13,225 each person. We have five main workers that are general manager, administration manager, operational manager, marketing manager and financial manager.